Case Report: Targeting 2 Antigens as a Promising Strategy in Mixed Phenotype Acute Leukemia: Combination of Blinatumomab With Gemtuzumab Ozogamicin in an Infant With a KMT2A-Rearranged Leukemia - Brethon, Benoît; Lainey, Elodie; Caye-Eude, Aurélie; Grain, Audrey; Fenneteau, Odile; Yakouben, Karima; Roupret-Serzec, Julie; Le Mouel, Lou; Cavé, Hélène; Baruchel, André (Frontiers in Oncology, 2021)
Mixed phenotype acute leukemia (MPAL) accounts for 2-5% of leukemia in children. MPAL are at higher risk of induction failure. Lineage switch (B to M or vice versa) or persistence of only the lymphoid or myeloid clone is frequently observed in biphenotypic/bilineal cases, highlighting their lineage plasticity. The prognosis of MPAL remains bleak, with an event-free survival (EFS) of less than 50% in children. A lymphoid-type therapeutic approach appears to be more effective but failures to achieve complete remission (CR) remain significant. KMT2A fusions account for 75-80% of leukemia in infants under one year of age and remains a major pejorative prognostic factor in the Interfant-06 protocol with a 6 years EFS of only 36%. The search for other therapeutic approaches, in particular immunotherapies that are able to eradicate all MPAL clones, is a major issue. We describe here the feasibility and tolerance of the combination of 2 targeted immunotherapies, blinatumomab and Gemtuzumab Ozogamicin, in a 4 years old infant with a primary refractory KTM2A-rearranged MPAL. Our main concern was to determine how to associate these 2 immunotherapies and we describe how we decided to do it with the parents’ agreement. The good MRD response on the 2 clones made it possible to continue the curative intent with a hematopoietic stem cell transplant at 9 months of age. Despite a relapse at M11 post-transplant because of the recurrence of a pro-B clone retaining the initial lymphoid phenotype, the child is now 36 months old, in persistent negative MRD CR2 for 12 months after a salvage chemotherapy and an autologous CAR T cells infusion, with no known sequelae to date. This case study can thus lead to the idea of a sequential combination of 2 immunotherapies targeting 2 distinct leukemic subclones (or even a single biphenotypic clone), as a potential one to be tested prospectively in children MPAL and even possibly all KMT2A-rearranged infant ALL.